Transvaginal Ultrasound Evaluation Of Cesarean Section Niche Scar During Pregnancy: A Prospective Longitudinal Study - Abdel-Rahman, Ahmed Morsy Saad; Hassanin, Tamer Mahmoud zaki (International Journal of Membrane Science and Technology, 2023)
Background and Objectives: To determine the prevalence of a CS scar niche during pregnancy using transvaginal ultrasound imaging, and to determine the relationship between the evolution of the CS scar niche and the ultimate pregnancy result. Materials and Methods: Transvaginal sonography was used in this prospective observational research to look at the uterine scars of 100 women at 11+0-13+6, 18+0-20+6 and 32+0-35+6 weeks of pregnancy. When the region of hypoechogenic myometrial discontinuity of the lower uterine section was discovered, a scar was discernible while pregnant. An indentation at the location of the CS scar with a depth of at least 2 mm in the sagittal axis was designated as the CS scar niche (or "defect"). Myometrial thickness next to the niche and the remaining myometrial thickness were used to quantify the hypoechogenic portion of the CS niche in two dimensions. (RMT). The entire lower uterine segment (LUS) thickness and the myometrial layer thickness were measured during the second and third trimesters of pregnancy at the thinnest portion of the scar area. In a non-selected subset of patients (n=20), CS scars were measured by two separate examiners. Scar visibility was evaluated using descriptive analysis, and the intraclass correlation coefficient (ICC) was computed to demonstrate the degree of absolute agreement between two observers for measuring scars. Maternal age, BMI, smoking status, prior vaginal deliveries, obstetric complications, and a history of uterine curettage were among the factors looked into as potential contributors to the CS scar niche. The hospital's computerized medical database provided clinical statistics on pregnancy outcomes and complications. Results: 80.9% of the ladies could see the scar. A CS scar niche was prevalent in 53.6% of people with a noticeable CS scar. Excellent intra- and interobserver agreement was observed for CS scar niche readings. There was no statistically significant correlation between maternal age, BMI, gestational diabetes, smoking status, previous vaginal delivery after CS, and niche development when subgroups of women were compared in terms of CS scar niche and non-niche. In contrast to 34.4 % of the women who did not have uterine curettage, 56.3% of the women who had done uterine curettage had uterine scar niches. Conclusions: The CS scar niche could be reproducibly measured by a transvaginal scan in half of the cases with a visible CS scar at the first trimester of pregnancy, according to an ultrasonography evaluation. An increased chance of uterine niche formation in a subsequent pregnancy was linked to prior uterine curettage. The CS scar area may be connected to uterine scar dehiscence.